Semen quality, infertility and mortality in the USA - Eisenberg, Michael L. (Oxford University Press, 2014)
STUDY QUESTION: What is the relationship between semen parameters and mortality in men evaluated for infertility? SUMMARY ANSWER: Among men undergoing an infertility evaluation, those with abnormal semen parameters have a higher risk of death, suggesting a possible common etiology between infertility and mortality. WHAT IS KNOWN ALREADY: Conflicting data exist that suggest either an inverse relationship or no relationship between semen quality and mortality. STUDY DESIGN, SIZE, DURATION: A study cohort was identified from two centers, each specializing in infertility care. In California, we identified men with data from 1994 to 2011 in the Stanford Reproductive Endocrinology and Infertility semen database. In Texas, we identified men with data from 1989 to 2009 contained in the andrology database at the Baylor College of Medicine Special Procedures Laboratory who were evaluated for infertility. Mortality was determined by data linkage to the National Death Index or Social Security Death Index. Comorbidity was estimated based on calculation of the Charlson Comorbidity Index or Centers for Medicare & Medicaid Services-Hierarchical Condition Categories Model. PARTICIPANTS/MATERIALS, SETTING, METHODS: In all, 11 935 men were evaluated for infertility from 1989 to 2011. During 92 104 person years of follow-up, 69 of 11 935 men died (0.58%). The mean age at infertility evaluation was 36.6 years with a mean follow-up of 7.7 years. MAIN RESULTS AND THE ROLE OF CHANCE: Compared with the general population, men evaluated for infertility had a lower risk of death with 69 deaths observed compared with 176.7 expected (Standardized mortality rate 0.39, 95% CI 0.30–0.49). When stratified by semen parameters, however, men with impaired semen parameters (i.e. male factor infertility) had significantly higher mortality rates compared with men with normal parameters (i.e. no male factor infertility). Low semen volume, sperm concentration, sperm motility, total sperm count and total motile sperm count were all associated with higher risk of death. In contrast, abnormal sperm morphology was not associated with mortality. While adjusting for current health status attenuated the association between semen parameters and mortality, men with two or more abnormal semen parameters still had a 2.3-fold higher risk of death compared with men with normal semen (95% CI 1.12–4.65). LIMITATIONS, REASONS FOR CAUTION: Our cohort represents infertile men, which may limit generalizability. As comorbidity relied on administrative data, granular information on each man regarding infertility diagnosis and lifestyle factors was unavailable. WIDER IMPLICATIONS OF THE FINDINGS: Men with impaired semen parameters have an increased mortality rate in the years following an infertility evaluation suggesting semen quality may provide a marker of health. STUDY FUNDING/COMPETING INTEREST(S): This study is supported in part by P01HD36289 from the Eunice Kennedy Shriver National Institute for Child Health and Human Development, National Institutes of Health (to D.J.L. and L.I.L.). The project was also partially supported by an NIH CTSA award number UL1 RR025744. None of the authors has any conflict of interest to declare.